WAQF, SHARIA VENTURE CAPITAL, AND INSTITUTIONAL PROBLEMS: SOCIO-LEGAL CASES IN INDONESIA - JM Muslimin; Bahrul Qamar; Hasbi Sen (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2022)
The purpose of this article is to indicate that the development of venture waqf so far in Indonesia is still not optimal. It is due to several obstacles, mainly socio-legal and managerial problems. Hence efforts are needed to continue to develop the concept of sharia venture waqf to more accelerate and overcome those obstacles. One of the efforts is by integrating and collaborating with commercial financial institutions, including through Sharia venture financing which is one of the tools in the Islamic economic concept to solve investment problems. In turn, the paper provides and prescribes a reconstruction and innovation of a comprehensive understanding and workable frame of agenda to be implemented in order to revitalize sharia venture waqf as a feasible financial instrument. The result of this research is sharia venture capital company is a form of financial institution that can act as a legal entity that adopt the concept of cash waqf. It is hoped that the optimization of the development of venture waqf can be easily realized. Likewise, several obstacles such as legal protection of cash waqf, issues of socialization, human resources, management systems, and accountability will also be easier to solve with the concept of integration.